Finite-time stabilization of switched linear systems and its application in terminal guidance. (30th November 2016) - Guo, Yang; Hu, Xiaoxiang; Deng, Biao; Zhang, Shuai; Jiang, Yu
This article presents finite-time stabilization methods of switched linear systems with disturbances. After extending finite-time stabilization and finite-time boundedness definitions to switched linear systems, sufficient conditions guaranteeing system finite-time boundedness are proposed, by which the state feedback controller method is obtained. For a class of switched terminal guidance systems, the methods are illustrated by application to guidance design to solve the finite-time stabilization problem considering nonzero initial conditions and state constraints.